PCR & Go: A Pre-installed Expression Chassis for Facile Integration of Multi-Gene Biosynthetic Pathways - Qi, Mingming; Zhang, Bei; Jiang, Lihong; Xu, Saijuan; Dong, Chang; Du, Yi-Ling; Zhou, Zhan; Huang, Lei; Xu, Zhinan; Lian, Jiazhang (Frontiers in Bioengineering and Biotechnology, 2021)
The introduction of multi-gene metabolic pathways is generally the first step for the construction of microbial cell factories and plays an essential role in metabolic engineering and synthetic biology. Here, we developed a “PCR & Go” system for facile integration and assembly of multi-gene pathways into the chromosome of Saccharomyces cerevisiae. The core component of the “PCR & Go” system was an expression chassis, where eight promoter/terminator pairs were pre-installed into the yeast chromosome and PCR amplified gene fragments could be inserted directly for functional expression. In combination with the CRISPR/Cas9 system and a gRNA plasmid library, the β-carotene (three genes), zeaxanthin (four genes), and astaxanthin (five genes) biosynthetic pathways were integrated and assembled into the yeast genome with an efficiency of ~93%, ~85%, and 69%, respectively, using PCR amplified gene fragments with ~40 bp homology arms in a single step. Therefore, the “PCR & Go” system can be used for fast construction of yeast cell factories harboring multi-gene pathways with high efficiency and flexibility.